2010
DOI: 10.1017/s1743921310015620
|View full text |Cite
|
Sign up to set email alerts
|

The stability of astrophysical jets

Abstract: Abstract. Jets are produced by young stellar objects (YSOs), by black hole binary star system "microquasars" (µQSOs), by active galactic nuclei (AGN), are associated with neutron stars and pulsar wind nebulae (PWNe), and are thought responsible for the gamma-ray bursts (GRBs). An understanding of these outflows must include how they are launched and collimated into jets, and how they propagate to large distances. Jets be they Poynting flux and/or kinetic flux dominated are current driven (CD) and/or Kelvin-Hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 87 publications
0
18
0
Order By: Relevance
“…CDI in magnetized flows has been studied from an analytical perspective in the non-relativistic regime by a number of authors. 7 Results show that this instability becomes dominant at large values of helicity (ratio between the toroidal and poloidal field components) and it is stabilised by a strong poloidal magnetic field. Under the physical conditions typical of jets close to the forming regions, CDI is expected to be dominant, though with small growth rates.…”
Section: The Sub-parsec Scales: Current-driven Instabilitymentioning
confidence: 90%
See 2 more Smart Citations
“…CDI in magnetized flows has been studied from an analytical perspective in the non-relativistic regime by a number of authors. 7 Results show that this instability becomes dominant at large values of helicity (ratio between the toroidal and poloidal field components) and it is stabilised by a strong poloidal magnetic field. Under the physical conditions typical of jets close to the forming regions, CDI is expected to be dominant, though with small growth rates.…”
Section: The Sub-parsec Scales: Current-driven Instabilitymentioning
confidence: 90%
“…Under the physical conditions typical of jets close to the forming regions, CDI is expected to be dominant, though with small growth rates. 7 In the relativistic regime, numerical simulations of static columns have shown that growth rates decrease with decreasing Alfvén speed and, regarding the non-linear regime, an increasing helicity of the magnetic field with increasing radius in the jet, stabilises the flow with respect to kink CDI. 9 The introduction of a sub-Alfvénic velocity shear generates important differences in the growth of this instability: In the case that the shear is inside the characteristic radius of the static column, the plasma flows through a temporally growing kink, whereas if the shear is outside that radius, the kink is advected with the flow and grows in distance.…”
Section: The Sub-parsec Scales: Current-driven Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases-remarkably, those corresponding to cold, Poynting-flux-dominated jets PK02 and PK03-the pinch exerted at some points of the jet axis during this transient phase (due to the coupling of the sideways oscillation caused by the jet overpressure with current driven instabilities, CDI; see, e.g., [18]) decelerates the flow to subsonic speeds and breaks the flow collimation beyond some axial distance (note, however, that since our simulations are axisymmetric, they are free of three-dimensional CDI, as the kink instability).…”
Section: Effects Of the Shear Layer On Poynting-flux-dominated Jetsmentioning
confidence: 99%
“…Numerical experiments have shown that the CDI growth rates are reduced in the case of magnetized flows with parallel magnetic fields or flows shrouded by (magnetized) winds [18][19][20]. Kim et al [21] focussed on the stability of (non-relativistic) magnetized jets that carry no net electric current and do not have current sheets.…”
Section: Effects Of the Shear Layer On Poynting-flux-dominated Jetsmentioning
confidence: 99%